Efficacy of Argel (Solenostemma argel (Del) hayne) Shoots’ Extract in the Control of the Red Flour Beetle (Tribolium castaneum Herbst) - Sir El Khatim , Mohammed Osman Mohammed; Abdelbagi, Azhari Omer (University of Khartoum Journal of Agricultural Sciences, 2023)
Laboratory studies were conducted to evaluate the efficacy of aqueous and organic extracts of the argel (S. argel) shoots against the 4th larval instar and adult stages of the red flour beetle (Tribolium castaneum) in the Sudan. Argel shoots were extracted sequentially by organic solvents of increasing polarity (petroleum ether, ethyl acetate and ethanol) as well as directly by distilled water or ethanol. Extracts were tested at concentrations ranging between 1% and 10%. The evaluated efficacy parameters were mortality, repellency and antifeedant effects. The tests were conducted in Petri dishes (9 cm i.d) and plastic cups (capacity 200 ml) and the obtained data were subjected to the analysis of variance and to the probit analysis. The results of the mortality data indicated that petroleum ether extracts was the most potent against the 4 th larval instar of T.castaneum as shown by its low LD50 of 8.2%, while ethyl acetate extract was the most potent against the adult of this pest with an LD50 value of 16%. The results showed that various types of argel shoot extracts induced significant dose dependent repellency against the T. castaneum. The highest 24 hours repellency was caused by the petroleum ether extract on the adult stage of T. castaneum as indicated by its low ED50 value of 1.58%.The different argel shoot extracts induced significant antifeedant action against the test insect. The lowest feeding ratio (0.02) was recorded in ethyl acetate extract- treated crushed wheat grains